Pengaruh Orientasi Digital dan Pembelajaran Organisasi Terhadap Inovasi Digital di Lembaga Pelayanan Publik - Robertus Adi Nugroho (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The reform of public services and bureaucracy has been a long process in the journey of government in Indonesia. Bureaucratic reform in the perspective of state administration is an interesting study, because indeed in its development, public organization reform in Indonesia tends to lead to the New Public Management approach which prioritizes outcomes, innovation, and creativity, as well as the New Public Service approach which prioritizes public service innovation. In this era of change, workers in government institutions that serve the public are challenged to have innovative work behavior by maximizing digital technology. Various studies have proven that by increasing digital innovation, the performance of the organization and the human resources in it will also increase. To improve digital innovation behavior, there are various variables that must be considered, including digital orientation and the learning system of the organization. Therefore, this study seeks to examine the effect of digital orientation and organizational learning on digital innovation at the Surabaya City National Land Agency Office. The results of the study state that digital orientation and organizational learning have a positive and significant effect on digital innovation. This study provides advice for management or government officials engaged in public services to pay more attention to the orientation and organizational learning system to be able to support better innovation behavior and ultimately improve the quality of public services in Indonesia.